Galatians 2:15-21 and the Belhar Confession (1986) in dialogue - Cloete, Daan (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Tis article brings Gal 2:15-21 into dialogue with the Confession of belhar (1986). It starts off with the issue of the formation of confessions in Early Christianity and asks whether there could be a confession basic to or in the making in the Galatians passage. The Confession of belhar (1986) is structured around three concepts, namely, unity, reconciliation and justice within the South African context of the church's disunity with all its social consequences. Galatians reflects a critical and decisive period in the history of the Early Christianity as it struggles with the issue of justification. In this pericope Paul focuses on Justification by faith, but supports it with other concepts like grace, equality/unity and freedom. While these sets of concepts do not correspond with one another, they both reflect a crucial period of transformation in the history of the church.